Low cost emergency water purification technologies - Ray, Chittaranjan; Jain, Ravi 1935- (Butterworth-Heinemann, 2014)
Natural disasters, tornadoes, hurricanes, and floods are occurring with increasing frequency. In emergencies, pure drinking water is quickly the most important item. Low Cost Emergency Water Purification Technologies provides the tips and techniques for supplying potable drinking water at low cost in the direst circumstances. Succinct and readable, this manual describes the various options for correcting unsanitary or unsatisfactory drinking water. Several treatment methods for contaminated water are reviewed and the pros and cons of each are discussed. Covers long-term technologies including sand filtration, packaged filtration units, pressurized filtration systems and natural filtration Addresses short-term strategies such as reverse osmosis-based filtration, cartridge filtration systems, and solar pasteurizations systems Describes disinfection systems, energy-saving applications, cost considerations and HA/DR applications
Includes bibliographical references and index
Keywords: TECHNOLOGY & ENGINEERING / Environmental / General; Drinking water / Purification; Emergency water supply; Survival and emergency equipment; Water filters; Water / Purification; Trinkwasseraufbereitung; Drinking Water; Water Purification; Drinking water -- Purification; Water -- Purification